Correlation between Seminal Parameters and Response to InVitro Sperm Activation According to Age and Type of Infertility - H. Hilo, Sanabel; M-R Fakhrildin, Muhammad-Baqir; N. Alwachi, Sabah (Iraqi Journal of Science, 2023)
This study was aimed to investigate the effect of sperm parameters on the response to in vitro sperm activation (ISA) and to compare sperm parameters according to the age and type of infertility.One hundred twenty-eight subjects employed in this study, with age range (18-49) years and duration of infertility (1-28) years. From each subjects semen sample was obtained and seminal fluid analysis (SFA) was done. Simple medium for assisted reproductive techniques; (SMART) was used for in vitro sperm activation by direct swim-up technique and centrifugation Swim-Up technique. Sperm concentration, sperm motility (%), sperm grade activity (%), normal sperm morphology (%) and sperm agglutination (%) were assessed. Crude data were statistically analyzed. From the results of present study, it was appeared that most sperm parameters were significantly (P<0.05) enhanced post-activation in vitro as compared to pre-activation using SMART medium by direct swim-up technique and centrifugation Swim-Up technique. Sperm concentration for post-activation was significantly reduced (P<0.05) compared to pre-activation groups and the percentages of progressive sperm activity with grade A, total progressive sperm motility (grades A and B) and normal sperm morphology were significantly increased (P<0.05). Based on the results of this study, it can be concluded that sperm motility and concentration were considered most important parameters that have the importance of activation and sperm morphology one of the sperm parameters that have role of the influence on the sperm qualities after activation.